2014
DOI: 10.1007/s11430-014-5023-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aluminium dust on secondary organic aerosol formation in m-xylene/NO x photo-oxidation

Abstract: As an important anthropogenic volatile organic compound (VOC), m-xylene has attracted numerous attentions due to its potential in secondary organic aerosol (SOA) formation. In this study, effects of aluminium dust seeds (boehmite and alumina) on SOA yield and aerosol size in m-xylene/NO x photo-oxidation were investigated in a 2 m 3 smog chamber at 30°C and 50% relative humidity. Compared to the seed-free system, the presence of aluminium seeds resulted in an increase in the SOA yield, and also enhanced the O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The particle-phase C-N stretch has been also characterized in m-xylene photooxidation experiments with NH 3 addition and was suggested to account for nitrogen-containing compounds (Liu et al, 2015b). A smog chamber study also found that the coexistence of SO 2 and NH 3 substantially enhanced the formation of nitrogen-containing compounds from the photooxidation of toluene (Chu et al, 2016).…”
Section: Particle Chemical Composition In Nh 3 -Involved Photooxidationmentioning
confidence: 99%
See 2 more Smart Citations
“…The particle-phase C-N stretch has been also characterized in m-xylene photooxidation experiments with NH 3 addition and was suggested to account for nitrogen-containing compounds (Liu et al, 2015b). A smog chamber study also found that the coexistence of SO 2 and NH 3 substantially enhanced the formation of nitrogen-containing compounds from the photooxidation of toluene (Chu et al, 2016).…”
Section: Particle Chemical Composition In Nh 3 -Involved Photooxidationmentioning
confidence: 99%
“…In the current work, the presence of SO 2 could promote the increase in particle acidity. Elevating particle acidity could facilitate the reaction of NH 3 /NH + 4 with carbonyl-containing compounds, leading to the formation of nitrogen-containing organic compounds (Liu et al, 2015b).…”
Section: Particle Chemical Composition In Nh 3 -Involved Photooxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive laboratory studies were carried out to investigate SA formation on several kinds of synthetic dust particles. Dry dust particles can only adsorb a limited amount of trace gases because of limited reactive surface areas. However, increases in relative humidity (RH) can facilitate the uptake of SO 2 , NO 2 , NH 3 , and water-soluble volatile organic compounds (VOCs) on dust ,, and thereby leads to SA formation.…”
Section: Introductionmentioning
confidence: 99%